Hubungan antara Kecerdasan Emosional dengan Efektivitas Diskusi PBL secara Online Mahasiswa Kedokteran FKIK Untirta - Trisnasari, Erni; Krisnamurti, Desak Gede Budi; Nugraha, Ummu Zakiyatun Nisa (Tirtayasa Medical Journal, 2024)
Lack of learning motivation in discussion group members will cause students to contribute only little and less actively during discussion. Given the importance of group discussion learning method (PBL) in achieving medical learning CPL, the author is interested in conducting research into the relationship between emotional intelligence and the effectiveness of group discussions online in FKIK Untirta medical students. Research design method using cross sectional design, quantitative observational research. The researchers used a stratified random sampling technique on a medical student. The reseach uses two types of questionnaires; the adoption questionnaire of the Emotional Competence Inventory of Ini Kadek’s research, and the Tutorial Group Effectiveness Instrument (TGEI). Based on the results of the study, the majority of emotional intelligence were in the middle category with 50 respondents (53,2%), in the high category 44 respondents (46,8%), and no respondents in the low emotional intelligence category. PBL discussions conducted by medical students of FKIK Untirta have been conducted effectively (98,9%). Bivariate analysis using Fisher Exact Test, showed no relationship (p>0,05) between emotional intelligence and discussion effectiveness. The category of emotional intelligence in students is at a moderate leel, the PBL discussions are already running effectively. There was no relationship between emotional intelligence and effectiveness of PBL discussions.